2019
DOI: 10.1111/ppl.13051
|View full text |Cite
|
Sign up to set email alerts
|

The expression of TwDXS in the MEP pathway specifically affects the accumulation of triptolide

Abstract: 1‐Deoxy‐d‐xylulose‐5‐phosphate synthase (DXS) is the first enzyme in the plant 2‐C‐methyl‐d‐erythritol 4‐phosphate (MEP) pathway of terpenoid synthesis. TwDXS is a prominent protein in the Tripterygium wilfordii proteome, with especially high expression in the root periderm. It is significantly regulated by methyl jasmonate. Here, we studied the influence of TwDXS expression on bioactive terpenoids in T. wilfordii. Specific fragments of TwDXS (GenBank: AKP20998.1) with lengths of 2148 and 437 bp were amplified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Two TwDXS and one TwDXR gene were cloned from T. wilfordii , and the researchers verified their functions through colour complementation experiments 97 . Further overexpression (OE) and RNA-interference experiments confirmed that the expression of TwDXR affects the production of triptolide in T. wilfordii 98 . The TwHDR gene encodes the final enzyme of the MEP pathway, which is very important for regulating isoprene biosynthesis.…”
Section: Biosynthesis Of Triptolidementioning
confidence: 84%
“…Two TwDXS and one TwDXR gene were cloned from T. wilfordii , and the researchers verified their functions through colour complementation experiments 97 . Further overexpression (OE) and RNA-interference experiments confirmed that the expression of TwDXR affects the production of triptolide in T. wilfordii 98 . The TwHDR gene encodes the final enzyme of the MEP pathway, which is very important for regulating isoprene biosynthesis.…”
Section: Biosynthesis Of Triptolidementioning
confidence: 84%
“…ApDXS encoded a protein of 691aa long which is in the range of plant DXSs. In general, the plant DXS protein ranged from 691 to 738aa long [19,20,[39][40][41]. The deduced amino acid sequence upon BLAST showed high similarities with plant DXS super family genes, indicating its close proximity to other functional DXS proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced production of these compounds, particularly diterpene lactones can be achieved through genetic manipulation of biosynthetic pathway [15,16]. The DXS gene has made known to be a significant target for the manipulation of terpenoids biosynthesis [17][18][19][20][21]. It is essential to detect the amino acid residues prerequisite to preserve the structure and function of DXS.…”
Section: Introductionmentioning
confidence: 99%
“…The first two rate‐limiting enzymes in this pathway are 1‐deoxy‐ d ‐xylulose‐5‐phosphate synthase (DXS) and 1‐deoxy‐d‐xylulose‐5‐phosphate reductoisomerase (DXR). GA‐3‐P and pyruvate could be converted into MEP through catalysis by DXS and DXR, sequentially 45,46 . In 2015, genes encoding Tw DXS and Tw DXR were cloned from T. wilfordii , and they were all highly expressed in the roots 47 .…”
Section: Biosynthesismentioning
confidence: 99%